Karakteristik Teh Herbal Bubuk Bunga Wijaya Kusuma (Epiphyllum Oxypetalum) Dengan Variasi Suhu Pengeringan - Pramesti, Rika Charina Dyah; Anggreni, A. A Made Dewi; Wijaya, I Made Mahaputra (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Wijaya kusuma flower contains phytochemical compounds including saponins, glycosides, steroids, terpenoids, phenolic compounds, resins, and tannins. . This study aims to find out the effect of drying temperature variations on the characteristics of wijaya kusuma flower powder herbal tea and determine the drying temperature that can produce wijaya kusuma flower powder herbal tea with the best characteristics. This study uses a Group Random Design with one factor, namely the variation of drying temperature consisting of 5 levels, namely 50°C, 60°C, 70°C, 80°C, and 90°C. The data produced was analyzed using Analysis of variance (ANOVA), if the treatment given showed an influence on the variables tested, then a further test was carried out BNJ (Honest Real Difference) at the level of 5%. The variables measured included yield, extract content in water, total phenols, total flavonoids, antioxidant activity, sensory tests, and antibacterial activity. The results showed that the variation in drying temperature had a significant influence on all the variables observed. The best treatment based on the effectiveness index test was a temperature of 50°C with the following characteristics: yield 15.67 ± 3.79%, extract content in water 6,39 ± 0,01%, total phenol 784.7±91.18 mg GAE/g, total flavonoids 48.83±2.08 mg QE/g, antioxidant activity 37.04 ± 6.89 ppm, antibacterial activity of Staphylococcus aureus 27.14 ± 2.28 mm, and overall acceptance of the panelists liked with a score of 3.35±0.186.